K. H. Ting as a 'modern' theologian: structure and contributions, limitations and legacy. Issue 1 (2nd January 2016) - Wickeri, Philip L.
ABSTRACT: K. H. Ting (丁光訓, 1915–2012) was the most important church-based theologian in China over the last three decades. His understanding of theology, from his student years in the 1930s to the end of his life, was distinctively 'modern, ' insofar as he accepted both the modern developments in theology that began in the eighteenth century, and the modern agenda of those who sought to reform China, politically, socially and culturally. My understanding of 'modern' is related to secularization theory and the way it has both been embraced by and challenges Christian theology. Ting's modern emphasis helps to explain his support for the Chinese Communist Party, his approach to church leadership, and his political and social role in the era of 'Reform and Openness.' What is important about K. H. Ting's modern theology is its structure, not the depth and creativity of his theological ideas, but the breadth and comprehensiveness of his theological activity. I interpret his theological structure ecclesiastically, ecumenically, politically, socially and culturally as a comprehensive approach to church renewal, openness and reform. Ting's modern theology and social thought may be contrasted with both 'premodern' and 'postmodern' approaches. A focus on the modern structure of Ting's theology will help us better understand his contributions and limitations, and his place in Chinese Christianity and society.